1969
DOI: 10.1111/j.1475-682x.1969.tb00938.x
|View full text |Cite
|
Sign up to set email alerts
|

The Search for Community Leaders: A Re‐examination of the Reputational Technique*

Abstract: A method similar to Bonjean's modification of the traditional reputational approach was applied to a study of two small communities within a Southern state. The relative absence of concealed and symbolic leaders suggests that leader visibility is a variable which varies systematically from community to community. Several community characteristics are posited as explanatory variables determining leader visibility.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1972
1972
1989
1989

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…8 Based upon 6 There is no concensus regarding the degree to which these three strategies tap community power. For example, several efforts have found these methods tend to "overlap" (e.g., French, 1969;Presthus, 1964;Preston, 1969aPreston, , 1969b while other studies have found that using different approaches results in defining different structures (e.g., Polsby, 1963;Agger et al, 1964;Fox, 1969Fox, , 1971Curtis and Petras, 1970). 7 Data were also collected on decision making activity associated with other local development efforts as well as on local decision making in general.…”
Section: Journal Of the Community Development Societymentioning
confidence: 96%
“…8 Based upon 6 There is no concensus regarding the degree to which these three strategies tap community power. For example, several efforts have found these methods tend to "overlap" (e.g., French, 1969;Presthus, 1964;Preston, 1969aPreston, , 1969b while other studies have found that using different approaches results in defining different structures (e.g., Polsby, 1963;Agger et al, 1964;Fox, 1969Fox, , 1971Curtis and Petras, 1970). 7 Data were also collected on decision making activity associated with other local development efforts as well as on local decision making in general.…”
Section: Journal Of the Community Development Societymentioning
confidence: 96%